ANALISIS PENERAPAN PRINSIP-PRINSIP MANAJEMEN PADA TRC BINTAN RESORT - Putu Della Rahayu; Andri Wibowo (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze the implementation of management principles at TRC Bintan Resort in the post–COVID-19 period, focusing on the functions of planning, organizing, leading, and controlling. The study employed a qualitative descriptive approach with a case study design. Data were collected through interviews, observations, and documentation involving the resort owner and employees directly engaged in daily operations. The findings reveal that the implementation of management functions at TRC Bintan Resort has not been optimal. This is indicated by the absence of formal strategic planning, the lack of an established organizational structure, the predominance of informal leadership practices, and supervisory mechanisms that are not based on performance indicators. These conditions reflect a gap between ideal management principles and actual managerial practices, which negatively affects operational effectiveness and service quality in the post-pandemic context. The study concludes that strengthening managerial functions through simple yet systematic management practices is essential to improve performance, competitiveness, and long-term sustainability of TRC Bintan Resort as a medium-scale hospitality business in a tourist destination area.